PEMBELAJARAN SAINS ANAK USIA DINI DENGAN KONSEP EMPAT PILAR PENDIDIKAN - Wisnu Budi Wijaya I Komang; Sri Darmayanti Ni Wayan; Gautama Jayadiningrat Made (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Science has great benefits in technological development and human welfare. Besides that, every day and around us we are always exposed to scientific phenomena. Therefore, the concept of science should be instilled in children from early childhood, moreover that is the golden age where children are experiencing optimal development. Learning science can be done using the concept of the four pillars of education, namely learn to know, learn to do, learn to be and learn to live together. The application of the concept of the four pillars of education is carried out specifically and adapts to the concept of science and does not ignore the character of early childhood. The role of parents and teachers in science learning for early childhood is as a learning resource, learning planner, motivator, facilitator and evaluator.